A rare case of pancreatic injury with transection of main pancreatic duct managed conservatively - Ghuge, Ashutosh; Sonarkar, Rajiv; Gedam, Bapuji S; Gajendra, Giriraj (Indian Journal of Case Reports, 2018)
An isolated injury to the pancreas is uncommon and the management remains controversial. The integrity of the main pancreatic duct is considered the most important determinant for prognosis. Physical signs and laboratory parameters are often inaccurate, and missing the diagnosis can cause serious clinical problems. We report a case of a 20-year-old man with blunt abdominal trauma. Pancreatic injuries although uncommon should be considered in the differential diagnosis in case of blunt abdominal trauma. Furthermore, the clinician should be aware that when pancreatic injuries are managed conservatively, the clinical, radiological, and laboratory parameters need to be monitored until resolution.